American Sign Language Syntax and Analogical Reasoning Skills Are Influenced by Early Acquisition and Age of Entry to Signing Schools for the Deaf - Henner, Jon; Caldwell-Harris, Catherine L.; Novogrodsky, Rama; Hoffmeister, Robert (Frontiers in Psychology, 2016)
Failing to acquire language in early childhood because of language deprivation is a rare and exceptional event, except in one population. Deaf children who grow up without access to indirect language through listening, speech-reading, or sign language experience language deprivation. Studies of Deaf adults have revealed that late acquisition of sign language is associated with lasting deficits. However, much remains unknown about language deprivation in Deaf children, allowing myths and misunderstandings regarding sign language to flourish. To fill this gap, we examined signing ability in a large naturalistic sample of Deaf children attending schools for the Deaf where American Sign Language (ASL) is used by peers and teachers. Ability in ASL was measured using a syntactic judgment test and language-based analogical reasoning test, which are two sub-tests of the ASL Assessment Inventory. The influence of two age-related variables were examined: whether or not ASL was acquired from birth in the home from one or more Deaf parents, and the age of entry to the school for the Deaf. Note that for nonnative signers, this latter variable is often the age of first systematic exposure to ASL. Both of these types of age-dependent language experiences influenced subsequent signing ability. Scores on the two tasks declined with increasing age of school entry. The influence of age of starting school was not linear. Test scores were generally lower for Deaf children who entered the school of assessment after the age of 12. The positive influence of signing from birth was found for students at all ages tested (7;6-18;5 years old) and for children of all age-of-entry groupings. Our results reflect a continuum of outcomes which show that experience with language is a continuous variable that is sensitive to maturational age.